2013
DOI: 10.4040/jkan.2013.43.2.267
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Medication Self-management Education Program for Elders with Hypertension Living in the Community

Abstract: 연구의 필요성서구화된 Evaluation of a Medication Self-management Education Program for Elders with Hypertension Living in the CommunityLee, Jong KyungDepartment of Nursing, College of Medicine, Dankook University, Cheonan, KoreaPurpose: The purpose of this study was to examine the effect of a medication self-management education program on medication awareness, communication with health care provider, medication misuse behavior, and blood pressure in elders with hypertension. Methods: The research design for this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
3
2
0
3
Order By: Relevance
“…This study also showed a significant reduction in medication misuse behavior in the experimental group after the AMAEP, with a pre- and post-average difference of −3.36. This is similar to the −2.81 point reduction in a study by Lee [ 11 ] and the −2.00 point difference in a study by Park et al [ 40 ] after conducting an educational program on drug misuse among older adults. The reduction in drug misuse may have been because patients with liver disease were discouraged from taking various dietary supplements or over-the-counter medications without consulting a healthcare practitioner in a number of sessions and through one-on-one education with the nurses.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This study also showed a significant reduction in medication misuse behavior in the experimental group after the AMAEP, with a pre- and post-average difference of −3.36. This is similar to the −2.81 point reduction in a study by Lee [ 11 ] and the −2.00 point difference in a study by Park et al [ 40 ] after conducting an educational program on drug misuse among older adults. The reduction in drug misuse may have been because patients with liver disease were discouraged from taking various dietary supplements or over-the-counter medications without consulting a healthcare practitioner in a number of sessions and through one-on-one education with the nurses.…”
Section: Discussionsupporting
confidence: 88%
“…Although OTC preparations may be relatively safe for healthy younger adults, they often create problems for chronic disease patients, particularly with pathologic conditions and combined with other substances (e.g., nonsteroidal anti-inflammatory drugs, herbs) [ 10 ]. Therefore, it is crucial for patients to communicate with a medical professional before taking OTC medications [ 11 ] and for patients to be educated about their disease because patients with more knowledge of their disease and better awareness of the state of their health tend to be more actively engaged in their treatment [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of more, most of the randomized controlled trials reported significant reduction of SBP and DBP in patients who had received self-management educational programs [30][31][32][33], summarized in one meta-analysis [11]. In study by Lee, self-care educational intervention was not successful in terms of BP control improvement among community-dwelling elderly subjects [34]. This is consistent with a previous study that was conducted in health care centers [35].…”
Section: Discussionsupporting
confidence: 77%
“…The physical and mental health levels of older adults living alone were poorer than those of older adults living with their families [35][36][37]. One study also reported that many ageing individuals were using medication that had expired because they had difficulty reading the expiry date on the package label [38].…”
Section: Discussionmentioning
confidence: 99%